Characterization of chimeric enzyme generated swapping human topoisomerase 1B N-terminal domain with Plasmodium falciparum counterpart and investigation of the interaction of human topoisomerase 1B with novel inhibitor derived from Antarctic invertebrates - CHHETRI SOREN, BINI (Università degli Studi di Roma "Tor Vergata", 2018)
Plasmodium falciparum is a protozoan parasite that causes malaria, one of the most frequent acquired red blood cell diseases worldwide. The emergence of multi drug resistant strains has increased the need to identify new molecular targets for anti-malarial therapy. DNA topoisomerases may be considered possible candidates, due to their important role in cellular activities, including DNA replication. DNA topoisomerase 1 relaxes supercoiled DNA by a transient DNA strand breakage, rotation, and religation. The 3D structure of the human topoisomerase 1- DNA complex identifies two domains forming a conserved protein clamp, tightly wrapped around the DNA duplex and an extended coiled-coil linker domain that appropriately positions the C-terminal active site tyrosine against the core to form the catalytic pocket. The N-terminal domain of human topoisomerase 1 is the only part of the enzyme that is still not crystallized and the function of this domain is not fully known. It has been suggested that the N-terminal domain of human topoisomerase 1B contribute little to the enzyme activity but recent studies show that this domain significantly modulates in vitro DNA relaxation. The Plasmodium falciparum topoisomerase 1 contains a shorter N-terminal domain, compared to the human homologue. This finding pushed us in exploiting its structural and functional properties in enzyme activity by swapping the human N-terminal domain with the corresponding one from Plasmodium falciparum. The chimeric enzyme has been functionally characterized in this thesis opening a route for the identification of new species selective drugs. In this thesis, I have also screened novel inhibitors of human topoisomerase 1B derived from Antarctic sponge Artemisina plumosa. The geographical and evolutionary history of the Antarctica results in a unique and isolated ecosystem rich in different kinds of organisms that can develop natural products and metabolites having distinctive and specific biological activities. Analysis of these metabolites can be ...